2020
DOI: 10.1111/1468-5922.12616
|View full text |Cite
|
Sign up to set email alerts
|

Healing cultural trauma and its application to the Router programme

Abstract: This paper explores the issue of cultural trauma, which is an area of concern in psychology generally and has emerged as one within the International Association for Analytical Psychology's Router training programme. A summary of responses to the issues of cultural trauma and complexes (alongside cultural differences) within analytical psychology are presented, followed by an overview of findings from the IAAP's evaluation of the Router training programme. These findings are then aligned with contemporary soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Given that current research indicates the COVID‐19 pandemic can lead to vicarious traumatization (Li et al 2020 ) and post‐traumatic stress symptoms (Sun, L. et al 2020b ; Yin et al 2020 ), it is worth noting that trauma can be mitigated through online work (Merchant 2020 ). Lazar and Hirsch ( 2012 ) found that Holocaust trauma in a Jewish‐Israeli context could be processed through online forums.…”
Section: Relevant Research Findings In Response To the Covid‐19 Pandemicmentioning
confidence: 99%
“…Given that current research indicates the COVID‐19 pandemic can lead to vicarious traumatization (Li et al 2020 ) and post‐traumatic stress symptoms (Sun, L. et al 2020b ; Yin et al 2020 ), it is worth noting that trauma can be mitigated through online work (Merchant 2020 ). Lazar and Hirsch ( 2012 ) found that Holocaust trauma in a Jewish‐Israeli context could be processed through online forums.…”
Section: Relevant Research Findings In Response To the Covid‐19 Pandemicmentioning
confidence: 99%